Metabolic Side Effects of Olanzapine in Patients With Psychotic Disorders in Oman: A Retrospective Cohort Study. (November 2022) - Al-Tobi, Zainab; Al Suleimani, Yousuf; Al-Rasadi, Khalid; Al-Shabibi, Saud; Al Mahrizi, Anwar; Al-Maqbali, Juhaina; Al-Waili, Khalid; Al-Adawi, Samir; Al-Zakwani, Ibrahim
We evaluated the impact of olanzapine on metabolic changes in patients with psychotic disorders. This was a retrospective cohort study involving patients prescribed olanzapine and attending Sultan Qaboos University Hospital (Muscat, Oman). Patients were followed up retrospectively from March 2006 until April 2021. Cardiovascular treatment targets were evaluated as per the 2019 European Society of Cardiology guidelines. We enrolled 253 patients (mean age: 40±17 years). Olanzapine monotherapy was associated with increased body weight (+8 kg; 95% confidence interval (CI): 6–9; P < .001), body mass index (+3 kg/m 2 ; 95% CI: 2–4; P < .001), total cholesterol (+.4 mmol/L; 95% CI: .3–.5; P < .001), low-density lipoprotein cholesterol (LDL-C) (+.3 mmol/L; 95% CI: .1–.4; P < .001), fasting triglycerides (+.2 mmol/L; 95% CI: .1–.3; P<.001), fasting glucose (+.6 mmol/L; 95% CI: .4–.7; P < .001), HbA1c (+.3%; 95% CI: .2–.4; P < .001), systolic blood pressure (BP) (+9 mmHg; 95% CI: 6–12; P < .001) and diastolic BP (+4 mmHg; 95% CI: 2–6; P < .001) levels. Cardiovascular therapeutic goals were attained in 38% (n = 97), 61% (n = 154), 71% (n = 180), and 59% (n = 150) for LDL-C, non–high-density lipoprotein cholesterol, triglycerides, and BP, respectively. Olanzapine was associated with adverse metabolic changes. Therefore, many patients were not at their target cardiovascular treatment goals.